Seismicity of La Réunion island - Duputel, Zacharie; Ferrazzini, Valérie; Lengliné, Olivier; Michon, Laurent; Fontaine, Fabrice R.; Massin, Frédérick (Comptes Rendus. Géoscience, 2021)
The island of La Réunion is made up of two main shield volcanoes: Piton des Neiges and Piton de la Fournaise. A wide variety of seismic events is observed, including but not limited to: tectonic events, volcano-tectonic earthquakes, volcanic tremors, long-period and very-long-period earthquakes. The seismicity of La Réunion island illuminates different levels of its volcanic plumbing system. In the shallowest part of Piton de la Fournaise, earthquakes are clustered below the volcano summit area and often occur as intense seismic swarms during magma intrusions. Seismic activity is also observed below the East flank of Piton de la Fournaise, shaping an eastward dipping structure possibly accommodating seaward displacements of the volcano. At larger depths, episodes of upward seismicity migrations indicate magmatic recharges of the shallow reservoir from deeper parts of the volcano plumbing system. Earthquakes are also observed below the oceanic crust in a zone of underplating between Piton des Neiges and Piton de la Fournaise. A major event at Piton de la Fournaise was the collapse of its summit caldera in April 2007. This activity resulting in a summital depression of 330 m was accompanied by very-long-period earthquakes with magnitudes ranging from $M_W=4.4$ to $M_W=5.4$. Another noticeable activity in La Réunion island is an active seismic swarm located within the oceanic crust under the North flank of Piton des Neiges. The origin of this sustained seismic activity is still unclear and is currently investigated, thanks to the deployments of additional stations in the region.